Analisis dan Perancangan Sistem Reservasi Paket Wisata Untuk Internal Karyawan PT. Garuda Maintenance Facility (GMF) Tbk - Angelina Ervina Jeanette Egeten; Lya Santi Rahayu; Riansyah Rafsanjani (Universitas Bumigora, 2019)
PT. Garuda Maintenance Facility (GMF) is a member of Garuda Indonesia, which provides free ticket facilities every year for its permanent employees. However, most of its employees have problems in making tour package reservations due to the lack of knowledge of tourist attractions. The purpose of this research is to provide solutions for PT. GMF employees in making tour package reservations, and it can be the solution for Koperasi Karyawan Garuda Maintenance Facility AeroAsia Sejahtera (KopKar GMF AAS) business opportunities in tourism sector. This research is using the interview method, observation, and literature review to compile the research supporting data, whereas the analysis method and design is using object-oriented analysis and design (OOAD). The result of this research is a form of system design which provides convenience for the employees who are making tour package reservations, as well as a business solution for KopKar GMF AAS. PT. GMF employees as the user of the tour package reservations user, and KopKar GMF AAS as the admin (administrator) of the system. The analysis and the development of this tour package reservations system include four main processes, which are creating travel plan, booking the travel package, payment confirmation, and managing transactions.